[PP.10.20] FLUORESCENCE ANALYSIS OF URINE SAMPLES FOR EVALUATION OF PHARMACOLOGICAL ADHERENCE IN RESISTANT HYPERTENSION. (September 2016) - Corrêa, N. Batista; de Faria, A.P.; Ritter, A.M.V.; Sabbatini, A.R.; Almeida, A.R.; Brunelli, V.; Barbaro, N.R.; Catharina, A.S.; Moreno, H.; Modolo, R.G.P.
Abstract : Objective: Resistant hypertensive subjects (RH) present blood pressure (BP) above 140/90 mmHg, despite the use of three or more antihypertensive agents of different classes, including if possible a diuretic. The lack of BP control caused by non-adherence to medication can be falsely interpreted as resistance to drug treatment. Although it is well established that adherence to treatment is critical to achieve BP control, some practical difficulties, such as application of a direct and simple method with low cost and feasibility in the clinical setting still happen. Our goal was to test a simple method to evaluate the medication adherence of RH. Design and method: Twenty-one patients referred to the Resistant Hypertension Clinic (Campinas, Brazil) had the triamterene included in their current prescription and were followed for 30 days period. We performed two random home visits to collect urine samples and test whether the patient took the medication in that day. Office BP, ambulatory BP monitoring (ABPM), home BP measurement (HBPM), biochemical data, and Morisky Adherence Scale (MMAS-8) were systematically acquired. Triamterene and its metabolite were measured by fluorimetric method. According to the fluorescence of urine, the subjects were divided between adherent and nonadherent. Results: We found 9 compliant patients and 12 (57%) non-adherents. No differences were found between groups with respect to baseline characteristics or medications in use; the Kappa test showed concordance between MMAS-8 and fluorescence methods by 0.61 (95% CI 0.28–0.94; p < 0.01).Non-adherent patients had higher office (81 ± 11 vs 73 ± 6 mmHg, p = 0.03), baseline 24-h ABPM (75 ± 9 vs 66 ± 7 mmHg, p = 0.01), post protocol 24-h ABPM (74 ± 9 vs 67 ± 6 mmHg, p = 0.03) and HBPM (77 ± 9 vs 67 ± 8 mmHg, p = 0.01) than their counterparts. Conclusions: Non-adherence to antihypertensive therapy is prevalent in resistant hypertension even if the patients are followed-up in specialized clinics. The fluorimetry method to detect triamterene intake in RH showed to be safe, feasible and easy to assess non-adherence and also associated with clinical parameter.